Modern methodological approaches to the study of the interrelation between everyday discourse about ethnic identity and contextual posts of the mass communication - F. A. Barkov (Vestnik MGIMO-Universiteta)
The article deals with the theoretical aspects of the transformation of mass media messages about situations of ethnocultural contact in the public discourse about ethnicity. The author presents a classification and brief description of the main information genres forming public discourse about ethnicity and the elements of a discourse analysis of news.